The last twilight - Liu, Marjorie M. (Liu, Marjorie M. Dirk & Steele novel., 2011)
"Duty called Dr. Rikki Kinn to the Congo. One of the world's top virus hunters working for the CDC, she is on a mission to investigate a deadly new plague. But there are those determined to stop her--at any price. Shape-shifter Amiri was born in this land of untamed splendor. Here he woke with the sun and raced as the cheetah...until he was kidnapped and subjected to terrible experiments by the evil Consortium. Now his colleagues and brothers in Dirk & Steele want him to return to Africa to face his nightmares. For a good woman has been targeted for death--a beautiful healer who holds the fate of millions in her hands, whose destiny is intertwined with his--and whose need leaves Amiri vulnerable, threatening his heart, his passion--and his soul."--P. [4] of cover.